Chromatographic Residue Analysis of Profenofos and Carbosulfan in Indian Major Carp, Labeo rohita (Hamilton) - Nagaraju Bantu (Journal of Stress Physiology & Biochemistry, 2020)
Fish live in the aquatic column; they are facing challenge for surviving from pollutants, particularly from various chemical fertilizers and pesticides used in or adjacent paddy fields or flood lands. They can be exposed to animals in a number of ways. Hence, an attempt has been made to know the presence of profenofos and carbosulfan residues in different tissues viz., liver, muscle, gill and kidney of Labeo rohita exposed to sublethal and lethal concentrations for 15 days. The results of the present study revealed that, prolonged exposure to sublethal concentrations of profenofos and carbosulfan in Labeo rohita leads to increased accumulation of residue. Thus repeated or continuous exposure to low concentrations of pesticides can lead to high residue concentrations without mortalities. Thus the uptake and persistence of profenofos and carbosulfan depends not only on a number of physical and chemical conditions but also varies according to the biological conditions.